Dynamics of Customary Land Rights for Public Interest in Indonesia - Marizal, M; Aulia Pravasta Indrianingrum; Hilman Rigel Nugroho (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
Customary land which is one part of the customary law community has a large and significant role in the existence of the existence of the customary law community in an area. It is undeniable that land is an important element for meeting the needs and achieving the level of welfare of each person, including customary law communities. Utilization of ulayat land or called ulayat rights owned by indigenous peoples is actually used and intended for the welfare of indigenous peoples. Basically, the use of ulayat land in Indonesia is carried out based on the communal style (togetherness) which is one of the characteristics of customary law communities. Along with the times, with the limited amount of land in the territory of Indonesia, but collided with the increase in the number of people and population density that continues to increase, it has implications for the discovery of customary land uses carried out by other than customary law communities. The dynamics that often become a problem in the utilization of customary land are interesting to be studied in more depth. This type of research belongs to the type of normative juridical, with the research method used in compiling this paper is descriptive-qualitative method. Keywords: Customary Law Community, Communal Land, Customary Rights